Discrimination and its relation to psychosocial well‐being among diverse youth in Sweden. Issue 176 (26th February 2021) - Gyberg, Fanny; Svensson, Ylva; Wängqvist, Maria; Syed, Moin
Abstract: Experiences of discrimination and links to well‐being have been examined extensively, but several gaps remain. The current study addresses four of those gaps by (1) examining both aggregated and source‐specific forms of discrimination, (2) comparing the experiences of minority and majority group members, (3) expanding the range of outcomes to include socially and developmentally appropriate measures, and (4) conducting the study in Sweden, a context in which discrimination and well‐being are not well understood. The sample consisted of 573 adolescents and emerging adults (71% women, M age = 19.21 years) who completed survey measures of discrimination and psychosocial well‐being (self‐esteem, life satisfaction, school adjustment, and identity distress). Findings indicated that minority groups reported more frequent discrimination, and more often cited ethnicity as the source of discrimination, whereas majority groups most often cited gender. Experiencing discrimination was related to poorer psychosocial well‐being similarly for all groups. Youth experiencing ethnic discrimination were more often subjected to multiple forms of discrimination compared with those subjected to other forms of discrimination. Taken together, this study brings important information on the complexity of discrimination among youth in the multicultural context of migration in Sweden.